The Intensive Halaqah Method as an Effort to Strengthen Qur’anic Memorization among Students at Jilussalamah Al-Islami Islamic Boarding School - Wahidi, Ridhoul; Nasrullah , Nasrullah; Amaruddin, Amaruddin; Syafril , Syafril; Khairudin, Fiddian; Murni , Dewi; Nalaysah Lubhna; Helma Puspita Sari; Rahmawati , Siti; Ilahi , Rahmad (Jurnal Masyarakat Mengabdi, 2025)
This study explores the implementation of the intensive halaqah method as an effort to strengthen Qur'an memorization among students at Jilussalamah al-Islami Islamic Boarding School. The background of this research arises from a common phenomenon in pesantren, where some students struggle to maintain consistency in memorization due to weak time management, limited methods, and insufficient personal guidance. The intensive halaqah method was chosen because of its advantages in creating a conducive, systematic learning environment and emphasizing collaboration between teachers and students. This study employed a qualitative-descriptive approach using observation, interviews, and documentation as data collection techniques. The research subjects were tahfiz students who participated in intensive halaqah sessions for one semester. The findings revealed that this method enhanced the quality of memorization, accelerated target achievement, and strengthened the students' spiritual motivation. Furthermore, the strong social interaction within the halaqah fostered a sense of solidarity and mutual support among the students. These findings highlight the significance of methodological innovations in Qur'anic learning to produce proficient and ethically grounded Qur'an memorizers.